Enhancement of detachment control with simplified real-time modelling on the KSTAR tokamak. (1st July 2022) - Eldon, D; Anand, H; Bak, J-G; Barr, J; Hahn, S-H; Jeong, J H; Kim, H-S; Lee, H H; Leonard, A W; Sammuli, B; Shin, G W; Wang, H Q
Abstract: Detachment control based on ion saturation current I sat measurements from Langmuir probes (LPs) is implemented in the KSTAR tokamak and shown to be capable of following dynamic and constant target trajectories with good accuracy, in H-mode, by moderating the flow rate of nitrogen or deuterium. I sat controllers normalize I sat in order to form attachment fraction ( A frac ) as their control parameter. The KSTAR implementation of A frac control differs from previous work in that it continuously calculates a model for attached I sat and uses that as the denominator in A frac, whereas prior implementations either record peak I sat at rollover as they pass it or take estimated I s a t, r o l l o v e r as a manual input prior to the shot. The KSTAR controller therefore does not need to keep track of rollover status and keep separate targets for pre- and post-rollover states, and it can automatically adapt to changes in scenario at any time. It is also less vulnerable to noise as it will not lock in an outlier as a rollover point.